Influence of magnetic water on early-age shrinkage cracking of concrete. (30th August 2017) - Wei, Huinan; Wang, Youkai; Luo, Jianjun
Highlights: Proper use of magnetic water can improve the shrinkage cracking resistance of concrete. The compressive and split strength of concrete mixed with magnetic water increased greatly. The length of magnetic field is critical for the growth of concrete strength. Magnetic field can change the surface tension and conductivity of water. The microstructure of concrete mixed with magnetic water is denser than concrete mixed with tap water. Abstract: This research investigates the shrinkage cracking of concrete, which were mixed with magnetic water. Magnetic water was obtained by the independent designed magnetizing equipment. Ring-test method and flat-test method were used to test early-age shrinkage cracking of concrete. Results show that the strain rate factor ( α ) and the total cracking area of unit area ( c ) of concrete were decreased when used magnetic water, which means the early-age shrinkage cracking resistance of concrete mixed with magnetic water is improved than those mixed with tap water. The best increase in early-age shrinkage cracking resistance of concrete is achieved when the magnetic strength is 260 mT and the length of magnetic field is 280 mm. Additionally, the compressive and split strength of concrete mixed with magnetic water increased greatly. It is also found that the length of magnetic field have direct effect on the growth of concrete strength.